(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An outbreak investigation was conducted in poultry farms of two Upazilas (Bograsadar & Sherpur) of Bogra district of Bangladesh to identify potential risk factors associated with occurrence of Infectious Bursal Disease (IBD)/Gumboro during February-March 2015. A total of 75 farms were recruited under a cross-sectional study of which 40% (n=30) ‘infected farms’ and 60% (n=45) ‘non infected farms’ from the 2 Upazilas. The infected farms were included from active and passive surveillance data of two Upazila Livestock Offices and District Veterinary Hospital (DVH), Bogra. The non-infected farms were included by convenient sampling technique from the same areas of the two Upazila. The data were collected from the poultry farms using pretested semi-structured questionnaire. A total of 75 farmers were interviewed of which 87% (n=67) male farmers, 11% (n=8) female farmers with an average age of 38(±9) years. Sixty percent (n=45) famers were rearing Sonali type of bird with a flock size 1554(±745) and 40% (n=30) farmers with broiler type of bird with a farm size 828(±263). Among the infected farms, 86.67% (n=26) farms were infected in Sadar Upazila and 13.37% (n=4) farms infected in Sherpur Upazila. The case fatality rate in Broiler and Sonali were 47.47%, 30.32% respectively with an average 33.26%. The study found that 26.67% (n=20) farms had practiced daily disinfection and 34.67% (n= 26) farms did not allow visitors in the farms. The potential risk factors relating to biosecurity aspects were found significant in this study at level of p≤0.05, were, “not practicing all in all out”(OR= 11.15, 95% CI= 2.03-61.16, p= 0.006), “not practicing cleaning and disinfection daily”(OR=7.92, 95% CI=1.2-52.28, p=0.03), “having partial netting of the farm” (OR= 36.97, 95% CI= 3.40-402.40, p=0.003) along with “inappropriate gap between two production cycle” (OR= 15.40, 95% CI= 2.27-99.57, p=0.005). The results from PE presented that good quality chicks (DOCs), farm bio-security, detection of antibody titerat day 1 in conjunction with implementing proper vaccination schedule to be followed for successful IBD prevention and control at the farm level. In conclusion, proper bio-security measures with strict vaccination protocol should be maintained mandatorily to control of IBD at the poultry farm in this district. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 182-189